Development of Multimedia Based Busy Book Learning Media to Improve Cognitive and Language Abilities in Early Childhood - Indyani, Wiwit; Kurniah, Nina (IJOEM Indonesian Journal of E-learning and Multimedia, 2024)
This study aimed to provide multimedia-based busy book learning resources to enhance the language and cognitive abilities of young children attending Bengkulu City's Lembayung Indah Kindergarten. Both books and multimedia-based busy books are the end products of this research project. Potential and problems, data collection, initial product design, expert validation, design revision, small group trials, product revision I, large group trials, product revision II, and final product are the ten steps that make up this research, which is a development research (Research & Development) using the Borg and Gall model. 36 youngsters made up the sample used in this study, which was selected at random. Children's abilities tests, open interviews, and observation were the methods used to get the data. T tests, percentages, and scores were employed in this study's data analysis. Based on the study's findings, the creation of multimedia-based busy book materials was deemed both practical and successful in enhancing the language and cognitive abilities of young children in group B of Lembayung Indah Kindergarten in Bengkulu City.